Australia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Using official data from the Australian Bureau of Economic Statistics and a formal growth accounting framework, this paper shows that the rapid accumulation of information processing and communication technology (ICT) capital over the last two decades in Australia has played a significant role in explaining the impressive, structural acceleration of labor productivity. The following statistical data are also included: household income, expenditure and savings, labor market, fiscal indicators, credit aggregates, capital and financial account, external assets and liabilities, export by commodity group, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet